Vitamin D Poisoning; Hypercalcemia in a Case with Richter Transformation : Vitamine D Poisoning; Hipercalcemia - Biberoglu, Serap; Cakmak, Fatih; Ozkan, Seda; Ikizceli, Ibrahim; Ipekci, Afsin (Acta Biomedica Atenei Parmensis, 2021)
In addition to modern medicine, the search for complementary and alternative medicine has been present for malignancy patients in every period. Confusion, polyuria, polydipsia, anorexia, vomiting, and muscle weakness are symptoms of acute poisoning and are related to hypercalcemia. In our case, a 52-year-old male patient applied to the Emergency Department(ED) with abdominal pain and weakness for two days. In this article, we wanted to present a case with vitamin D poisoning that occurs after the phytotherapy in a patient who developed chronic lymphocytic leukemia (CLL) to Richter transformation. In some patients, especially at ED, taking a high dose of vitamin D history can be challenging. In patients with hypercalcemia, a careful history should be taken, and it should be questioned as "Vitamin D use" rather than "Drug use" since families do not accept the vitamins as drugs.